Pengaruh Pelayanan Mobil Kas Keliling Bank Syariah Indonesia Terhadap Kepuasan Nasabah (Studi Pada Mahasiswa Universitas Muhammadiyah Riau - Rahayu, Norra Isnasia; Misral, Misral; Anriva, Della Hilia; Anugra, Putri Eriska (Akuntansi & Ekonomika, 2023)
This study aims to determine the effect of BSI's mobile cash car service on student satisfaction in paying tuition fees. This type of research is quantitative research with a survey approach. The population is University of Muhammadiyah Riau students, the sample is taken 100 respondents, with the Accidental Sampling technique. This study uses primary data obtained from respondents' answers in the form of filling out questionnaires, namely data obtained directly from the object of research. Data analysis techniques include: Simple Linear Regression, and hypothesis testing consisting of a t-test. The results for the t-test showed significant results from the count value of 20.808 greater than the thing 1.984 tables with a significant 0.000 smaller than the significant level value of 0.005 (5%) so that is seen from the regression value of 0.815 the positive effect.